Strategi Inovasi dan Kinerja Perusahaan Manufaktur di Indonesia: Pendekatan Model Simultan dan Model Sekuensial - Lena Ellitan (Jurnal Manajemen Maranatha, 2006)
Innovation is currently considered to be critical for organizational competitiveness and survival. There has been a mushrooming of conferences, courses, publications and event whole journals dedicated to the innovation issued including innovativeness and innovation strategy. This paper focusses on the effect of innovation strategy on firms’s performance. An innovation strategy for manufacturing function covers four areas: a firm’s desired innovation leadership orientation (i.e. being a leader versus a follower), its level of emphasis on process and product innovation, its use of internal and external sources of innovation and its intensity of investment in innovation. This study examines two models of the association between manufacturing firms’ innovation strategy and their financial performance. The first examines the variations in the firms’ financial performance as a function of the dimensions of innovation strategy. The second is a sequential model that suggests a causal consequency among the dimension of innovation strategy that may lead to higher performance. Data were collected through mailed questionnaires. Respondents were CEOs of medium and large manufacturing firms on Indonesia. The questionnaires were sent to 700 CEOs manufacturing firms, an 21.05% response rate. Test of non-response bias indicated that the sample is representative for this study. The findings of this study suggest that: (1) Innovation strategy is important factor and a determinant of financial performance, (2) both model are appropriate for examining the associations between the dimension of innovation strategy and firms’ performance, and (3) the sequential model provides additional insights into the indirect contribution of the individual dimensions of innovation strategy to firms’ performance.